MOVE AND STEP ANALYSIS OF THE TEXTUAL CONTENT ON THE OVERVIEW PAGE OF THE JUMEIRAH BALI WEBSITE - Alif Falah, Maftah; Paramarta, I Made Suta; Adnyani, Ni Luh Putu Sri (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
The tourism and hospitality industries are growing rapidly and are encouraging digital communication transformation. This study aims to examine the rhetorical structure in the form of moves and steps in the textual content of the Jumeirah Bali website, particularly the Overview page, using an established analytical framework of move analysis to map communicative units in the text. The data were analyzed qualitatively to identify the communicative units in each segment, including attracting attention, introducing features, narrating brand values, and encouraging booking actions. The result identified 10 moves and 10 steps on the Overview subpage, covering hotel descriptions, accommodation types or room categories, main facilities, and special offers (packages). Theoretically, these findings expand the application of move analysis from academic and professional texts to digital hospitality media. In practice, mapping moves and steps guides the design of user experience-oriented web content, namely by organizing essential information at the beginning, clarifying value propositions, and aligning calls to action with visitor needs.